2007
DOI: 10.1097/grf.0b013e31811eba5e
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia as a Treatment for Birth Asphyxia

Abstract: This chapter will report to the frequency of neonatal hypoxic-ischemic encephalopathy. The pathophysiology and the childhood outcome of encephalopathy due to hypoxia-ischemia will be examined. The limitations of current therapy for this condition and new therapies will be evaluated. Hypothermia seems to offer the most promise as a therapy for neuroprotection in hypoxic-ischemic encephalopathy. The evidence-based trials of hypothermia will be reviewed along with recommendations regarding clinical applications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…The combined findings stress the importance of comparing and contrasting HI injury in both preterm and term infants relative to follow-up morbidity, plasticity and long-term behavioral development. They also heighten the urgency to continue a search for neuroprotective interventions such as whole body/head cooling or erythropoietin in term HIE infants [9192]. Finally, our findings also show subtle but significant early RAP deficits and robust attention deficits in a preterm HI model, emphasizing the importance of developing new interventions for this population as well.…”
Section: 5 Conclusionsupporting
confidence: 59%
“…The combined findings stress the importance of comparing and contrasting HI injury in both preterm and term infants relative to follow-up morbidity, plasticity and long-term behavioral development. They also heighten the urgency to continue a search for neuroprotective interventions such as whole body/head cooling or erythropoietin in term HIE infants [9192]. Finally, our findings also show subtle but significant early RAP deficits and robust attention deficits in a preterm HI model, emphasizing the importance of developing new interventions for this population as well.…”
Section: 5 Conclusionsupporting
confidence: 59%
“…While a number of different agents have shown a neuroprotective effect in animal models of HI, hypothermia is the only therapeutic intervention that has been extensively investigated in the newborn patient population 8, 150-153. This clinical investigation was preceded by a large number of preclinical studies in multiple animal models that demonstrated a neuroprotective effect 90, 154-159.…”
Section: Mechanisms Of Hypothermic Protection In Hypoxia-ischemiamentioning
confidence: 99%
“…In birth asphyxia, the infant needs immediate professional care in the neonatal intensive care unit (NICU; Long & Brandon, 2007), and hypothermia treatment is a method for treating HIE following birth asphyxia (Shankaran & Laptook, 2007) to reduce the risk of brain injury (Yager, Armstrong, Jaharus, Saucier, & Wirrell, 2004). Hypothermia treatment was introduced in 2005 in several neonatal units in various countries that participated in Total Body Cooling trial (TOBY), an English multi-center study (Azzopardi et al, 2009).…”
mentioning
confidence: 99%